Cancer and apoptosis: The apoptotic activity of plant and marine natural products and their potential as targeted cancer therapeutics - Chaudhry, Gul-e-Saba; Md Akim, Abdah; Sung, Yeong Yik; Sifzizul, Tengku Muhammad Tengku (Frontiers in Pharmacology, 2022)
Cancer is a multifactorial, multi-stage disease, including complex cascades of signaling pathways—the cell growth governed by dysregulated and abrupt cell division. Due to the complexity and multi-regulatory cancer progression, cancer is still a challenging disease to treat and survive. The screening of extracts and fractions from plants and marine species might lead to the discovery of more effective compounds for cancer therapeutics. The isolated com-pounds and reformed analogs were known as future prospective contenders for anti-cancer chemotherapy. For example, Taxol, a po-tent mitotic inhibitor discovered from Taxus brevifolia, suppresses cell growth and arrest, induces apoptosis, and inhibits proliferation. Similarly, marine sponges show remarkable tumor chemo preven-tive and chemotherapeutic potential. However, there is limited re-search to date. Several plants and marine-derived anti-cancer com-pounds having the property to induce apoptosis have been approved for clinical trials. The anti-cancer activity kills the cell and slows the growth of cancer cells. Among cell death mechanisms, apoptosis induction is a more profound mechanism of cell death triggered by naturally isolated anti-cancer agents. Evading apoptosis is the major hurdle in killing cancer cells, a mechanism mainly regulated as in-trinsic and extrinsic. However, it is possible to modify the apopto-sis-resistant phenotype of the cell by altering many of these mecha-nisms. Various extracts and fractions successfully induce apoptosis, cell-cycle modulation, apoptosis, and anti-proliferative activity. Therefore, there is a pressing need to develop new anti-cancer drugs of natural origins to reduce the effects on normal cells. Here, we've emphasized the most critical elements: i) A better understanding of cancer progression and development and its origins, ii) Molecular strategies to inhibit the cell proliferation/ Carcino-genesis, iii) Criti-cal regulators of cancer cell proliferation and development, iv) Sig-naling Pathways in Apoptosis: Potential Targets for targeted thera-peutics, v) Why Apoptosis induction is mandatory for effective chemotherapy, vi) Plants extracts/fractions as potential apoptotic in-ducers, vii) Marine extracts as Apoptotic inducers, viii) Marine iso-lated Targeted compounds as Apoptotic inducers (FDA Ap-proved/treatment Phase). This study provides a potential therapeutic option for cancer, although more clinical studies are needed to veri-fy its efficacy in cancer chemotherapy.